Location Map - Point Lookout State Park (1977) (State of Maryland Department of Natural Resources, 1977)
Appears to be a location map for land acquisition for Point Lookout State Park. Map covers from St. Mary's City and south. Note says "total programmed acreage 705 acres". This is sheet 1 of 2. We do not have sheet 2.